Book review. Issue 1 (6th February 2018) - Longhurst, Phil
Abstract : Sustainable Solid Waste Management, is edited by a team of five experienced professionals with an enviable publication record across the breadth of academic and industrial fields of environmental engineering. This widely referenced, fully indexed, 728 page text book provides an all-encompassing pathway from introduction to advanced knowledge across the waste management sector. Accessible explanations and key principles make up a logical pattern of 22 chapters of technical, social and legal themes. Sponsored by the Environmental and Water Resources Institute of the American Society of Civil Engineers this is a significant undertaking to address a subject whose scope covers the disposal of all resources from manufacture, use and the final residue of materials within our commercial, industrial and municipal lives.